Physiological Cost Optimization for Sit-to-Stand Transfer - Mughal, A.M.; Iqbal, K. (2007 IEEE Region 5 Technical Conference, 2007)
Researchers have analyzed human movement coordination in a variety of ways using different optimization variables and functions. In this study we used a 4-link sagittal plane biomechanical model of sit-to-stand transfer to study physiological cost optimization. We regulated the movement with optimal controller design emulating central nervous system decision making. In such scheme the state and inputs were weighted by penalty functions derived from physiological variables, i.e., center of mass and ground reaction forces. We tracked the position variables through reference trajectories, which were also used to generate active components of joint torques. Net torque comprising feedback and feedforward components resulted in stable STS transfer. Our results shows that analytical model with physiological cost functions provides efficient framework for the study of STS movement.